Small Proline-Rich Protein 3 Regulates IL-33/ILC2 Axis to Promote Allergic Airway Inflammation - Zhu, Guiping; Cai, Hui; Ye, Ling; Mo, Yuqing; Zhu, Mengchan; Zeng, Yingying; Song, Xixi; Yang, Chengyu; Gao, Xin; Wang, Jian; Jin, Meiling (Frontiers in Immunology, 2022)
Small proline-rich proteins (SPRRs), components of cornified cell envelope precursors, have recently been found to participate in airway diseases. However, their role in allergic airway inflammatory conditions remains unknown. Here, we explored the expression of SPRR3 in house dust mite (HDM)-sensitized/challenged mice and attempted to elucidate the regulatory role of SPRR3 in allergic airway inflammation. SPRR3 was identified via bioinformatics analysis of Gene Expression Omnibus (GEO) databases and further confirmed to be upregulated in the lungs of asthmatic mice. Knockdown of SPRR3 via the intratracheal route significantly inhibited eosinophils in bronchoalveolar lavage fluid (BALF) and suppressed the expressions of type 2 cytokines (IL-4, IL-5, and IL-13) in BALF and lung tissues. Further, SPRR3 knockdown reduced the expression of IL-33 and further attenuated the activation of the PI3K/AKT/NF-κB signaling pathway in the recruitment of group 2 innate lymphoid cells (ILC2s) to inhibit allergic airway inflammation. In vitro, SPRR3 siRNA could alleviate HDM-induced inflammatory responses in BEAS-2B cells. This study reveals the regulatory role of SPRR3 in allergic airway inflammation, identifying this protein as a potential novel therapeutic target for asthma.